2022
DOI: 10.1155/2022/5942947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long‐Term Regular Continuous and Intermittent Walking on Oxidative Stress, Metabolic Profile, Heart Rate Variability, and Blood Pressure in Older Adults with Hypertension

Abstract: It is documented that regular exercise is beneficial for improving the antioxidant system, metabolic system, cardiac autonomic function, and blood pressure in those with hypertension. In this regard, low-intensity exercise is recommended for older adults, particularly those with chronic diseases. This study aimed to compare the effects of long-term regular continuous walking with intermittent walking on oxidative stress, metabolic profile, heart rate variability, and blood pressure in older adults with hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…The differences between the groups, however, were statistically insignificant with the exception of some clinical parameters (the triglycerides concentration, the ratio of the total cholesterol to HDL and the atherosclerogenic index were lower in the group walking continuously; p < 0.05). Thus, the study confirmed the advantageous influence of long-term and regular aerobic exercise of a low intensity on redox equilibrium in the venous blood of hypertensive subjects [ 99 ]. Tsarouhas et al, however, determined the total antioxidant capacity (TAC) in the serum of 20 males and 7 females (66.8 ± 13.1 years) with CHF subjected to effort, and 9 males and 3 females (67.0 ± 5.6 years) with the same disease without introducing a training program.…”
Section: Effects Of Physical Exercise On Redox Equilibrium In Cardiov...supporting
confidence: 66%
See 1 more Smart Citation
“…The differences between the groups, however, were statistically insignificant with the exception of some clinical parameters (the triglycerides concentration, the ratio of the total cholesterol to HDL and the atherosclerogenic index were lower in the group walking continuously; p < 0.05). Thus, the study confirmed the advantageous influence of long-term and regular aerobic exercise of a low intensity on redox equilibrium in the venous blood of hypertensive subjects [ 99 ]. Tsarouhas et al, however, determined the total antioxidant capacity (TAC) in the serum of 20 males and 7 females (66.8 ± 13.1 years) with CHF subjected to effort, and 9 males and 3 females (67.0 ± 5.6 years) with the same disease without introducing a training program.…”
Section: Effects Of Physical Exercise On Redox Equilibrium In Cardiov...supporting
confidence: 66%
“…CVDs are commonly characterized by glucose metabolic syndrome, oxidative stress and inflammation, whilst PA is known to improve redox status, insulin sensitivity and endothelial function [ 100 ]. The effects of PA on oxidant–antioxidant equilibrium can be ambiguous and depend on the duration and intensity of exercise; however, in general, they are positive [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ] ( Table 1 ). Physical exercise of different intensities (usually of moderate or of low intensity, and long term) is already widely recommended as an aid in the prevention and treatment of CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that regular physical exercise is a beneficial factor in the treatment of increased arterial blood pressure in human hypertension ( Prasertsri et al, 2022 ), and human and experimental arterial hypertension are related to oxidative stress. Moreover, in a previous study, it was observed that physical exercise ameliorates the oxidative stress in SHRs treated with a high fat- or fructose-enriched diet ( Szabó et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The RAS is involved in redirecting blood flow to the working muscles, ensuring adequate oxygen and nutrient supply. While the vasoconstrictive effects of angiotensin II, a key molecule in the RAS, may initially seem counterproductive during exercise, it is crucial to consider the overall picture [90]. The RAS activation leads to increased blood flow to the active muscles, allowing for efficient oxygen and nutrient delivery.…”
Section: Benefits Of Exercise In Blood Pressure Managementmentioning
confidence: 99%